The creation of interactive activity pods at a Recycling Education Centre. (May 2015) - Pickford, Tony; Ellis, Liz
This paper describes the creation of interactive, educational activity pods at an education centre at a recycling depot. The project originated from a new waste management contract between Cheshire West and Chester Council and May Gurney (now Keir Waste Management), which included the provision of educational facilities. Representatives from May Gurney and the council's waste management team approached the Faculty of Education & Children's Services looking for input into the proposed education centre to be set up in Winsford, Cheshire. An already existing module on Education for Sustainable Development was modified to enable trainee teachers on a specialist global learning route of an undergraduate programme to devise and create interactive exhibits and activities for the Centre. Although a quite unique opportunity to create learning resources about recycling issues, the process described in the paper illustrates ways in which higher education, the private sector and local authorities can co-operate effectively for mutual benefit and the benefit of learners. Trainees' ideas also illustrated ways in which the, sometimes quite abstract, concepts of Education for Sustainable Development can be translated into engaging activities with implications at local and more global levels.